Table of contents and introductory materials for Vol. 23, no. 5, 2017/2018 - Bruce Quantic (The Advocate, 2018)
This includes the table of contents, a message from the ATE-K president, and editorial information for vol. 23, issue 05 (Fall - Winter 2017/2018)